2018
DOI: 10.1111/jcpt.12665
|View full text |Cite
|
Sign up to set email alerts
|

Development and clinical application of an evidence-based pharmaceutical care service algorithm in acute coronary syndrome

Abstract: We developed a PCS algorithm for ACS based on the contents of evidence-based drug therapy and the core concept of pharmacist services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This result was consistent with the results of other studies assessing chronic conditions ( Hohmeier et al, 2019 ; Thompson et al, 2020 ; Wang et al, 2021 ). But limited studies showed the efficacy of MTM services in patients with non-chronic conditions, like cancer ( Dürr et al, 2021 ) and acute coronary syndrome ( Kang et al, 2018 ). These results showed possibility of heterogeneity in the type of diseases and indicated the need for additional evidence to support the efficacy of MTM services for managing patients with non-chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with the results of other studies assessing chronic conditions ( Hohmeier et al, 2019 ; Thompson et al, 2020 ; Wang et al, 2021 ). But limited studies showed the efficacy of MTM services in patients with non-chronic conditions, like cancer ( Dürr et al, 2021 ) and acute coronary syndrome ( Kang et al, 2018 ). These results showed possibility of heterogeneity in the type of diseases and indicated the need for additional evidence to support the efficacy of MTM services for managing patients with non-chronic disease.…”
Section: Discussionmentioning
confidence: 99%